Use of P1-P4 Purkinje reflections as a surrogate sign for intraoperative patient fixation. Issue 12 (December 2021) - Thompson, Vance; Holladay, Jack; Sretavan, David
Abstract : Circumferential, even anterior capsular overlap maximizes intraocular lens stability and posterior capsular opacification mitigation and provides best long-term outcomes for the cataract patient. P1 and P4 Purkinje reflections at patient fixation may provide a reliable marker for capsulotomy centration. However, patient fixation may be hindered during surgery because of anesthesia or light sensitivity. In this study, we demonstrate that the relationship between the P1 and P4 Purkinje reflections previewed prior to surgery when the patient is fixating may be recreated intraoperatively if fixation becomes difficult. The final position of P1 and P4 relative to one another at fixation is invariant in a given patient, but there are variations among patients. Knowledge of the P1 and P4 relationship can be used as a surrogate sign of patient fixation to assist in capsulotomy centration during cataract surgery.